Users' Perceptions of Signage Systems at Three Portuguese Hospitals - Rita Rodrigues (2020)
This article is a report on the quantitative data collected from patients, family members, and visitors using the outpatient areas of three hospitals in Portugal. It details the users' views regarding the existing signage and presents suggestions to improve the design and implementation of the signage systems. A questionnaire was used with 1,287 respondents. The results showed that almost all users had a positive opinion regarding the current signage. However, some of the users' answers and observed behaviors indicated that the majority tended to ignore the signs and preferred to ask staff for help. Additionally, when asked for suggestions, many of the respondents were able to point out existing problems that affected their wayfinding. Although the signage was generally evaluated as good, many of the users perceived a variety of problems and, as already mentioned, asked the staff for directions, which results in lost time and hidden costs for the institutions.